2023
DOI: 10.1017/wet.2023.40
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of herbicides for selective control of an invasive liana, old man’s beard (Clematis vitalba)

Brenda Jarvis-Lowry,
Kerry C. Harrington,
Hossein Ghanizadeh
et al.

Abstract: Old man’s beard is a woody liana that has become an invasive weed in many areas of its introduction, through its vigorous spread and negative impacts on the tree hosts it climbs. Control techniques that improve precision and reduce non-target damage are increasingly preferred for weed control yet have not been compared in published research for use against old man’s beard. Field experiments in New Zealand were conducted to: 1) assess targeted herbicide techniques for control of its climbing stems when growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 46 publications
3
4
0
Order By: Relevance
“…By June, most C. vitalba stems were still largely bare of leaves, and many seed heads had lost all their achenes, especially at S2. This is consistent with monthly dispersal observations of three other C. vitalba populations at different sites, where 60–85% of all achenes were lost between March and the end of June 2020 (Jarvis‐Lowry 2023). By September, most stems were vigorously producing new terminal and axillary growth.…”
Section: Methodssupporting
confidence: 89%
See 4 more Smart Citations
“…By June, most C. vitalba stems were still largely bare of leaves, and many seed heads had lost all their achenes, especially at S2. This is consistent with monthly dispersal observations of three other C. vitalba populations at different sites, where 60–85% of all achenes were lost between March and the end of June 2020 (Jarvis‐Lowry 2023). By September, most stems were vigorously producing new terminal and axillary growth.…”
Section: Methodssupporting
confidence: 89%
“…Thus, the Dark treatment may have been a simulation of conditions in the soil seed bank for that reason, as well as a lack of light. Indeed, Jarvis‐Lowry (2023) reported that fewer than 40% of C. vitalba seeds sown in field plots emerged as seedlings, which is similar to germination results in the Dark treatment of the current experiment.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations